Cult practice as a marker of religious identity - Riazanova, S.V. (Perm Federal Research Centre Journal, 2023)
The purpose of the article is to establish the specifics of a new religious group – the Intercession brotherhood – by analyzing its cultic practices. The community combines features of folk religiosity, new religious movements, and so-called «historical sects». The research is based on interviews and correspondence with former members of the community, acquaintances of the inhabitants of the monastery, the analysis of materials from a closed group in a social network, records of classes conducted by the leader of the monastery, and photocopies of the group’s workbooks. The Intercession monastery appears as a community of a closed type, which is manifested in the territorial and communication isolation of the residents of the communal estate, the practice of internal labor duties, and the idea of a group as a family. Orthodox rituals have been replaced by the mystical practice of fighting evil and eliminating the enemies of the commune. The practice of naming for adult members of the community, formation of new marriage unions, participation in gender-oriented councils created a special microenvironment leading to the unification of the worldview of believers. The presence of a system of privileges for advanced monks is complemented by a developed system of penalties, including public repentance, burial alive and expulsion from the monastery. In this version, the community is not a new religious movement, but a variant of the development of Orthodox life within the boundaries of modern culture.